Mw ≥ 5 aftershocks of the 2008 Sichuan earthquake: Analysis of temporal variation of Omori Law p-value - Gupta, Harsh K.; Rekapalli, Rajesh (Frontiers in Earth Science, 2022)
Strong to great earthquakes considerably weaken the structural strength of the subsurface strata and civil constructions. The occurrence of Mw ≥ 5 aftershocks further contributes to the loss of human lives and property damage. Therefore, the estimate of the duration of such aftershocks occurring near a metropolitan area is of major concern. In a previous study (Gupta et al 2008), aftershocks for the destructive Sichuan earthquake, China (12-05-2008 Mw7.9) for 23 days were used to estimate p-value and it was proposed that the M ≥ 5 aftershocks may continue for seven months. In the present study, we analyze Mw≥ 5 aftershocks for two-year duration within 300 km radius from the epicenter, using modified Omori Law, which is well-known for analyzing aftershock rate and duration. We compare our results with the duration of aftershocks estimated using the exponential scaling law for the M ≥ 5 aftershock duration for major to great Himalayan earthquakes. Our analysis suggests that high p-value (>1) indicates a slow decay of aftershocks as observed. As the p-value changes with time, the estimates of the duration of the occurrence of aftershocks of M ≥ 5 may change. Using a dynamic approach, the data of the first 100 days has been used in this study and estimated the duration of occurrence of Mw ≥ 5 earthquakes as ~300 days, which is found to be true. Our analysis suggests that the p-value temporal variation from the onset of the mainshock and the slope of its variation are the key elements in comprehending the duration of the occurrence of the aftershocks. We infer that a high p-value (p>1) after the main earthquake, indicates a longer duration of larger aftershocks, which has been found in the case of the Sichuan earthquake. The p-value decreases with time, however, an intermittent increase of p-value could indicate high probability of higher magnitude aftershock occurence The proposed dynamic approach of estimating temporal p-values may help in forecasting the occurrence of stronger aftershocks more effectively. We believe that this is the first time, when temporal variation of p-values is estimated and related with the occurrence of aftershocks.